Il Sacchi mi mandava tratto tratto de fasci di quelle strane, e mostruose opere di quel Teatro : Carlo Gozzi e il teatro spagnolo - SCANNAPIECO, ANNA (Florence Firenze University Press, 2020)
The contribution proposes a reflection on the greatest author of the 18th Century Italian theater who drew on the dramaturgical heritage of the siglos de oro. The main elements dealt with are: Carlo Gozzi's theoretical reflection on the characteristics of Spanish theater; the fundamental role in the repêchage that the actors of Antonio Sacco's company had in that theater, for which the author provided - according to him - a "voluntary friendly assistance"; finally, the most significant data that emerge, or could emerge, from the first National Edition of the works of Carlo Gozzi (launched in 2011).
Italian
Keywords: Spanish theatre; Carlo Gozzi; Antonio Sacco theatrical ideas